The association between burning mouth syndrome and urologic chronic pelvic pain syndrome: A case‐control study. (30th August 2020) - Crocetto, Felice; Coppola, Noemi; Barone, Biagio; Leuci, Stefania; Imbimbo, Ciro; Mignogna, Michele Davide
Abstract: Background: The overlap between some painful conditions is widespread. The aim of this study was to evaluate the overlap between burning mouth syndrome (BMS) and urological chronic pelvic pain syndrome (UCPPS) in an outpatient clinic of a university hospital. Methods: A controlled clinical study was performed. BMS patients and healthy controls were enrolled in the study. Patients were screened through laboratory test and a complete urological examination. Two validated questionnaires were submitted to all the patients: National Institutes of Health Chronic Prostatitis Symptom Index (NIH‐CPSI) and International Prostatic Symptom Score (IPSS). Results: A total of 50 BMS patients and 50 healthy controls were enrolled in the study. Statistically significant differences between the two groups regarding the items of the IPSS questionnaire of Incomplete Emptying (U = 750, P < .001), Intermittency (U = 768.5, P < .001), QoL (U = 848, P < .002), and Total Symptom score (U = 1040, P = .05) were found. Moreover, the responses of NIH‐CPSI showed statistically significant differences regarding Pain subscale (U = 714, P < .001), QoL Impact subscale (U = 1016.500, P = .05), and NIH‐CPSI total score (U = 953.500, P = .002). Conclusion: To the best our knowledge, the reported data demonstrate for the first time an association between BMS and UCPPS. Further studies with a larger sample are needed to confirm the co‐occurrence of urological symptoms in patients with burning mouth syndrome.